Monitoring A Nutrient Film Technique (NFT) Hydroponic System For Nutrient Delivery To Bokchoy Plants - Jaswin; Muhammad Khaerul Naim Mursalim; Raymond Erz Saragih (Journal of Digital Ecosystem for Natural Sustainability, 2026)
A small-scale Nutrient Film Technique (NFT) hydroponic system requires continuous monitoring because it strongly depends on nutrient solution flow, water availability, and the stability of operational parameters. Manual monitoring is often less effective because system disturbances may be detected too late by users. This study aims to design, implement, and test an Internet of Things (IoT)-based NFT hydroponic monitoring and automatic nutrient dosing system prototype capable of displaying data, storing monitoring history, providing warnings during abnormal conditions, and automatically dosing nutrient solution based on sensor readings. The method used is prototyping. The prototype integrates an NFT hydroponic system, IoT devices, Firebase, a web dashboard, Telegram notifications, an automatic nutrient dosing system, and supporting actuators. Test results show that the system is able to read and transmit monitoring data, display information on the dashboard, store historical data, and classify system conditions into normal, warning, and critical statuses based on predetermined thresholds. The system also successfully provides warnings through the dashboard, Telegram, and a local alarm when abnormal conditions are detected. The automatic nutrient dosing system, implemented using two G328 peristaltic pumps controlled via PID-based logic in response to TDS sensor readings, was successfully integrated and functioned as intended.